Sex differences in lipid metabolism and metabolic disease risk - Sugiyama, Michael G.; Agellon, Luis B. (Biochemistry and cell biology, 2012)
The ability of nutrients to regulate specific metabolic pathways is often overshadowed by their role in basic sustenance. Consequently, the mechanisms whereby these nutrients protect against or promote a variety of acquired metabolic syndromes remains poorly understood. Premenopausal women are generally protected from the adverse effects of obesity despite having a greater proportion of body fat than men. Menopause is often associated with a transformation in body fat morphology and a gradual increase in the susceptibility to metabolic complications, eventually reaching the point where women and men are at equal risk. These phenomena are not explained solely by changes in food preference or nutrient intake suggesting an important role for the sex hormones in regulating the metabolic fate of nutrients and protecting against metabolic disease pathophysiology. Here, we discuss how differences in the acquisition, trafficking, and subceullular metabolism of fats and other lipid soluble nutrients in major organ systems can create overt sex-specific phenotypes, modulate metabolic disease risk, and contribute to the rise in obesity in the modern sedentary climate. Identifying the molecular mechanisms underpinning sex differences in fat metabolism requires the unravelling of the interactions among sex chromosome effects, the hormonal milieu, and diet composition. Understanding the mechanisms that give rise to sex differences in metabolism will help to rationalize treatment strategies for the management of sex-specific metabolic disease risk factors.